Unweaving the web : deception and adaptation in future urban operations - Gerwehr, Scott, 1968-; Glenn, Russell W. (Rand, 2002)
Despite the realization that an urban environment can intensify the effects of deception in military operations, many important research questions remain unanswered, and even unasked. The authors use the well-developed literature on deception in animal biology to begin asking and answering those questions. This was done with the aim of improving the ability of U.S. forces to both conduct friendly deception and counter adversary deception in urban operations of all sorts. Using animal biology and military science as the source materials, the authors undertook to elaborate on existing deception theory and to propose new paths for technological, doctrinal, educational, and experimental development. The study concludes that in urban settings, there is great room for improvement in how U.S. forces do deception, and that it is imperative for them to better counter adversary deception. The study notes that deception methods are a preeminent form of adaptation in both biology and military operations, with the concluding chapter exploring this cross-disciplinary relationship (with a particular focus on counteradaptation as counterdeception).